RETRACTED: Nexus Between Green Finance, Energy Efficiency, and Carbon Emission: Covid-19 Implications From BRICS Countries - Xiaoxia Wang; Jiaoya Huang; Ziman Xiang; Jialiang Huang (Frontiers in Energy Research)
The threats of climatic change on life, health, and the environment have been regarded by the joint consensus of scholars in the recent decades. With the advancement of global green development, green finance has paved the way for the government to respond to the challenges of climate change by providing mature financial services, appropriate financing, investment, and project funds related to environmental protection. In this context, green finance was proposed, and the relationship between green finance, renewable energy, and carbon emissions in the BRICS countries from 2000 to 2018 was further studied based on the quantile regression model. The presence of cross-sectional dependence in panel results is tested through CD and LM methods. The findings show the negative effect of green finance and non-fossil energy consumption on CO2 emissions. Furthermore, economic growth, trade openness, energy consumption, and foreign direct investment increase the CO2 emissions. Finally, the research results confirm that green finance is the best financial strategy to reduce carbon dioxide emissions.